2009
DOI: 10.1002/ajmg.c.30231
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of cilia in disease: The human ciliopathies

Abstract: Ubiquitous in nature, cilia and flagella comprise nearly identical structures with similar functions. The most obvious example of the latter is motility: driving movement of the organism or particle flow across the epithelial surface in fixed structures. In vertebrates, such motile cilia are evident in the respiratory epithelia, ependyma, and oviducts. For over a century, non-motile cilia have been observed on the surface of most vertebrate cells but until recently their function has eluded us. Gathering evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
290
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 312 publications
(301 citation statements)
references
References 88 publications
3
290
0
8
Order By: Relevance
“…11 This presents as an atypical retinitis pigmentosa with early macular involvement. 12 The clinical manifestation is gradual onset of night blindness, followed by photophobia and loss of central and colour vision. 11 Many variants of the ophthalmological phenotype in BBS have been described and some patients develop the converse sequence of pathological events with early loss of cone photoreceptors followed by rod photoreceptors.…”
Section: Clinical Overviewmentioning
confidence: 99%
See 3 more Smart Citations
“…11 This presents as an atypical retinitis pigmentosa with early macular involvement. 12 The clinical manifestation is gradual onset of night blindness, followed by photophobia and loss of central and colour vision. 11 Many variants of the ophthalmological phenotype in BBS have been described and some patients develop the converse sequence of pathological events with early loss of cone photoreceptors followed by rod photoreceptors.…”
Section: Clinical Overviewmentioning
confidence: 99%
“…4 Electroretinography is the investigation of choice and may show early changes within the first two years of life, although significant changes are rarely visible before the age of five. 12 Symptoms usually develop in the first decade of life and most patients are legally blind by the second or third decade, 13 although moderate forms of the disease do exist. Other eye abnormalities such as cataracts and refractive errors are also prevalent in BBS.…”
Section: Clinical Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the skeletal and ectodermal anomalies, it has been referred to as cranioectodermal dysplasia (CED) [Gellis and Feingold, 1979;Savill et al, 1997;Tamai et al, 2002;Obikane et al, 2006;Fry et al, 2009;Konstantinidou et al, 2009], but for this study, we use the eponym Sensenbrenner syndrome. There is significant phenotypic variability and dramatic advances using microarray analysis and targeted-and whole-exome sequencing (WES) have demonstrated molecular heterogeneity [Gilissen et al, 2010;Walczak-Sztulpa et al, 2010;Arts et al, 2011;Bredrup et al, 2011;Hoffer et al, 2013], and showed that this syndrome is probably due to cilia dysfunction [Baker and Beales, 2009;Konstantinidou et al, 2009;Walczak-Sztulpa et al, 2010;Hildebrandt et al, 2011]. OMIM currently lists four molecular subtypes as CED1 (#218330, chr 3q221.3-q22.1, IFT122), CED2 (#613610, chr 2p24.1, WDR35), CED3 (#614099, chr 14q24.3, IFT43), and CED4 (#614378, chr 4p14, WDR19).…”
Section: Introductionmentioning
confidence: 99%